1979
DOI: 10.1113/jphysiol.1979.sp012935
|View full text |Cite
|
Sign up to set email alerts
|

The kinetics of tubocurarine action and restricted diffusion within the synaptic cleft.

Abstract: SUMMARY1. The kinetics of tubocurarine inhibition were studied at the post-synaptic membrane of frog skeletal muscle fibres. Acetylcholine (ACh) and (+ )-tubocurarine were ionophoresed from twin-barrel micropipettes, and the membrane potential of the muscle fibre was recorded intracellularly. Tubocurarine-receptor binding was measured by decreases in the response to identical pulses of ACh. 2. The responses to both ACh and tubocurarine had brief latencies and reached their maxima rapidly. It is suggested tha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
40
0
2

Year Published

1980
1980
2002
2002

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 69 publications
(47 citation statements)
references
References 55 publications
(97 reference statements)
5
40
0
2
Order By: Relevance
“…One method is to measure the rate of recovery of the response to an agonist following a brief ionophoretic application of tubocurarine (Castillo & Katz, 1957;Waud, 1967;Armstrong & Lester, 1979). However, it has been shown that rates measured in this way are likely to be limited by diffusion, even when the nerve terminal is lifted away from the endplate (Waud, 1967;Armstrong & Lester, 1979 Ginsborg & Stephenson (1974).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…One method is to measure the rate of recovery of the response to an agonist following a brief ionophoretic application of tubocurarine (Castillo & Katz, 1957;Waud, 1967;Armstrong & Lester, 1979). However, it has been shown that rates measured in this way are likely to be limited by diffusion, even when the nerve terminal is lifted away from the endplate (Waud, 1967;Armstrong & Lester, 1979 Ginsborg & Stephenson (1974).…”
Section: Discussionmentioning
confidence: 99%
“…However, it has been shown that rates measured in this way are likely to be limited by diffusion, even when the nerve terminal is lifted away from the endplate (Waud, 1967;Armstrong & Lester, 1979 Ginsborg & Stephenson (1974). They inferred that the halftime for dissociation of tubocurarine is around a millisecond in rat diaphragm endplates, and even briefer in amphibian endplates; that is, the dissociation rate constant is about 700 s-' in rat, and faster in amphibia.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Others explained this relationship using the concept of buffered diffusion. 19 The relationship, however, may also be explained by differences in pharmacokinetic behaviour between compounds. A more rapid initial decay of the plasma concentration coincides with a more rapid equilibration between plasma and biophase, with subsequent shortening of the onset time.…”
Section: Discussionmentioning
confidence: 99%
“…By comparing pulse responses of the model system with results obtained in real synapses (Armstrong & Lester, 1979), it is calculated that a steady terminal leakage could account for the extracellular curare if less than fifty curare releasing endings are formed by the injected neurone. However, if their number exceeds fifty then the 60P PROCEEDINGS OF THE PHYSIOLOGICAL SOCIETY, JUNE 1981 extracellular curare can only be explained by an (additional or exclusive) action potential-dependent release.…”
Section: Department Of Physiologymentioning
confidence: 99%